Avian influenza A H7N9 virus infections not evident among high-risk groups in India - Pawar, Shailesh D.; Tandale, Babasaheb V.; Mali, Rashmi S.; Potdar, Varsha A.; Kode, Sadhana S.; Biswas, Dipankar; Chadha, Mandeep S. (Indian journal of medical research (New Delhi, India : 1994), 2016)
The study was also approved by the Institutional Human Ethics Committee of the ICMR-National Institute of Virology at Pune, as per the guidelines laid down by the Indian Council of Medical Research for research on human subjects [4] . A total of 31 throat and nasal swab samples were collected from individuals with ILI and tested for the presence of influenza A virus using real-time reverse transcription polymerase chain reaction (qRT-PCR) as per the protocol recommended by the CDC, USA [12] . [...]an emergence of a novel avian-origin influenza A H7N9 virus in China has caused concern in the neighbouring countries.